High-Quality Early-Childhood Education at Scale: Evidence from a Multisite Randomized Trial - William Dougan; Jorge Luis García; Illia Polovnikov (Institute of Labor Economics (IZA), 2023)
We offer a new analysis of a large-scale trial of an early-childhood education program that targeted premature, low-birthweight children. This targeting heavily oversampled twins, whose outcomes differed significantly from singletons'. Singletons' gains in short-term cognition and age-18 non-cognitive skills were comparable to those of the Perry Preschool and Carolina Abecedarian Projects, supporting those programs' scalability. For twins, however, the program generated smaller positive short-term gains and negative age-18 impacts. These outcome differences arise from differences in parents' response to the program. A household production model suggests that the possibility of jointly supplying parenting to twins helps explain those differences.
Keywords: J13; I28; C93; H43; 330; childcare; early childhood education; large-scale randomized trial; parental investment; parenting